Statistical Estimation and Inference of Board Composition on Financial Performance of Oil and Gas Companies in Nigeria - Idi, Danjuma; Stephen, Mathew (Mikailalsys Journal of Mathematics and Statistics, 2024)
This study examines the relationship between board characteristics and financial performance of listed oil and gas firms in Nigeria, highlighting the gap in existing literature on the topic. The purpose of this study is to investigate the impact of board independence, board size, and gender diversity on financial performance. A sample of three listed oil and gas firms on the Nigerian Exchange Group (NGX) was selected, and secondary data from annual financial statements for 2010-2021 were analyzed using panel regression and correlation analysis. The findings reveal that female board members have a positive and significant impact on financial performance, while board independence and board size have a positive but insignificant impact. The study concludes that gender diversity on boards is a key factor in driving financial success, and recommends increasing the number of female board members to improve financial performance. The results contribute to the understanding of the relationship between board characteristics and financial performance in the Nigerian oil and gas industry.